Pemantauan Kelelahan Secara Langsung Melalui Moxy Monitor - Fadhli Munadi Manalu; Jajat Darajat Kusumah Negara; Agus Gumilar (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
Monitoring physiological responses in badminton athletes remains challenging because conventional methods are often unable to provide real-time information regarding local muscle oxygen utilization and fatigue development. This study aimed to examine the relationships among muscle oxygen saturation ratio (SmO₂ Ratio), Fatigue Index, and maximal oxygen uptake (VO₂Max) in badminton athletes using real-time muscle oxygenation monitoring. A quantitative correlational design was employed involving 10 competitive badminton athletes from PB Mutiara Cardinal, Bandung, Indonesia. Muscle oxygen saturation was measured using the MOXY Monitor based on Near-Infrared Spectroscopy (NIRS) technology, Fatigue Index was assessed through the Running Anaerobic Sprint Test (RAST), and VO₂Max was estimated using the 20-meter Multistage Shuttle Run Test. Data were analyzed using Pearson correlation, simple linear regression, multiple linear regression, and path analysis. The results showed that (1) SmO₂ Ratio was not significantly related to Fatigue Index (r = 0.463, p = 0.177); (2) SmO₂ Ratio was significantly associated with VO₂Max (r = 0.859, p = 0.001), explaining 73.8% of its variance; (3) Fatigue Index was also significantly related to VO₂Max (r = 0.763, p = 0.010); and (4) SmO₂ Ratio and Fatigue Index jointly explained 90.8% of the variance in VO₂Max. It can be concluded that SmO₂ Ratio is a strong physiological predictor of aerobic capacity and that real-time MOXY monitoring provides a practical approach for evaluating physiological status and supporting performance optimization in badminton athletes. Keywords: Badminton, Fatigue Index, Moxy Monitor, NIRS, Muscle Oxygen Saturation